TESL trainees' beliefs on teaching of grammar : Aspects amendable and resistant to change - Ting, Su Hie (2009)
The study examined TESL trainees' beliefs on the teaching of grammar, focussing on aspects which are amendable and resistant to change. Questionnaire data were collected from 67 TESL trainees (35 pre-service and 32 in-service) before and after a grammar teaching course in a TESL degree programme in a Malaysian university. The TESL trainees reported views that were already inclined towards the inductive teaching of grammar for meaningful communication in various contexts at the beginning of the course. However, the grammar teaching course increased awareness of the importance of grammatical competence and the explicit teaching of language structures in context. Beliefs on grammar teaching less amendable to change were views on grammar rule memorisation, accuracy-based drills and instantaneous error correction in oral activities. The implications of the findings on the impact of teaching the principles and practice of the communicative approach in TESL teacher education programme are discussed.